Fragments form the past an account of people and events in the Assemblies of Northern Scotland - Cordiner, James, 1877-1962 (London, UK Pickering and Inglis, 1961)
Includes photographs.
Brethren writers.
Keywords: Brethren movement -- Scotland -- history